2004
DOI: 10.1353/lan.2004.0157
|View full text |Cite
|
Sign up to set email alerts
|

Semantics and Pragmatics of English Verbal Dependent Coordination

Abstract: This article investigates coordination of verbal adjuncts and complements in English, considering coordinations of adjunct with adjunct, complement with complement, and adjunct with complement, for both non-WH and WH elements, using the conjunctions or, and, and but. Previous analyses have never to my knowledge covered all of these cases. It is shown that syntactic or (compositional) semantic constraints on coordination fail to cover all the facts, as do ambiguity-based explanations. Better (though still incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…[✓adj & adj] It is important to note right away, however, that not all varieties of English allow for coordination with optional arguments. My data work with informants indicates that some varieties of English only allow adjunct material to be coordinated (see also Whitman 2004Whitman -2007 for a speaker of such an idiolect) -i.e. some varieties of English are like Dutch (cf.…”
Section: Surface Variation In Coordinated Multiple Wh-questionsmentioning
confidence: 99%
See 4 more Smart Citations
“…[✓adj & adj] It is important to note right away, however, that not all varieties of English allow for coordination with optional arguments. My data work with informants indicates that some varieties of English only allow adjunct material to be coordinated (see also Whitman 2004Whitman -2007 for a speaker of such an idiolect) -i.e. some varieties of English are like Dutch (cf.…”
Section: Surface Variation In Coordinated Multiple Wh-questionsmentioning
confidence: 99%
“…(6 Before concluding this section, it must also be observed that in addition to the three types of languages in which CMWQs can be formed, there is also a fourth type, in which CMWQs cannot be formed at all. Japanese is an example of such a language (Whitman 2004(Whitman -2007, as well as Chinese. 2 To take stock so far, and to give an overview of the distribution of CMWQs among the languages that prominently figure in the discussion in this study, the following table summarizes the properties of the four types of CMWQ languages and constructions.…”
Section: Surface Variation In Coordinated Multiple Wh-questionsmentioning
confidence: 99%
See 3 more Smart Citations